Musculoskeletal adaptations to strength training in frail elderly: a matter of quantity or quality?. Issue 3 (24th February 2020) - Aas, Sigve N.; Breit, Markus; Karsrud, Stian; Aase, Ole J.; Rognlien, Simen H.; Cumming, Kristoffer T.; Reggiani, Carlo; Seynnes, Olivier; Rossi, Andrea P.; Toniolo, Luana; Raastad, Truls
Abstract: Background: The improvement in muscle strength generally exceeds the increase in muscle size following strength training in frail elderly, highlighting the complex aetiology of strength deficit in aging. The aim of this study was to investigate the effect of heavy‐load strength training on a broad number of factors related to specific strength in frail elderly. Methods: Thirty‐four frail elderly men ( n = 18) and women ( n = 16) aged 67 to 98 (86 ± 7 years) were randomized to either a group performing strength training twice a week for 10 weeks (ST) or a non‐exercising control group (CON). Knee extensor muscle strength was tested as one‐repetition maximum (1RM) and isometric maximal voluntary contraction (MVC) torque. Muscle activation was assessed by the interpolated twitch technique, and muscle density [mean Hounsfield units (HU)] and intermuscular adipose tissue (IMAT) by computed tomography scans of the quadriceps femoris. Muscle biopsies from the vastus lateralis were obtained to investigate changes in intramyocellular lipids and single‐fibre specific tension. Results: In ST, knee extension 1RM and MVC improved by 17 and 7%, respectively. Muscle cross‐sectional area of the quadriceps femoris increased by 7%, accompanied by a 4% increase of muscle density. No changes in IMAT, voluntary activation level, single‐fibre specific tension, or lipid content were observed. Conclusions: In contrast to several previous reports, the improvements in isometric muscle strength and muscle area were in good agreement in the present study. The training‐induced increase in muscle density was not due to changes in skeletal muscle lipid content. Instead, the increase in muscle density may reflect increased packing of contractile material or simply an increased ratio of muscle tissue relative to IMAT.